Pendidikan Profesi dan Pengabdian Masyarakat di Indonesia - Nurhayati; Rita Komalasari; Cecep Mustafa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
This paper presents for the first time the results of research related to the professional training of judges. The research method presented in this paper is a case study. Thirty-one judges, in the City and District Courts, were included to obtain various perspectives through interviews. The results of the study show that the influence of training can shape judicial interpretations of justice. We found that trainee judges studied the three most important forms of justice: legal justice, moral justice, and social justice. Judges will also learn from the training that judges will be asked to harmonize various dimensions of justice in the context of public service.